Synthesis, Characterization and Anticancer Activity of polyester Derived from Polyvinyl Alcohol with New Oxazolidine-5-one Derivatives - Talib, Elaf Noori; Younus, Maha A. (Iraqi Journal of Science, 2025)
In this study, compound [A], an oxime derivative, was synthesized through the reaction of 4-aminoacetophenone with hydroxylamine hydrochloride, using sodium acetate as a catalyst. Subsequently, Schiff bases [A1-A3] were prepared by reacting compound [A] with various aromatic aldehydes in the presence of glacial acetic acid. Acid derivatives containing oxazolidinone ring [A4- A6] were synthesized from the reaction of Schiff bases [A1- A3] with chloroacetic acid. The resulting compounds [A4-A6] reacted with thionyl chloride to produce the corresponding acid chloride [A7-A9]. Polyesters [A10-A12] were produced by reacting polyvinyl alcohol with compounds [A7-A9]. All prepared compounds were characterized using infrared spectroscopy FTIR and nuclear magnetic resonance NMR spectroscopy. Additionally, the anticancer activity of some of the prepared compounds (A10, A12) against liver cancer cell line  hepG2 was evaluated in vitro.